PERANGKAT EDUKASI DESAIN GRAFIS UNTUK MENUNJANG PERKEMBANGAN KBN MAHASISWA STEBI GLOBAL MULIA CIKARANG - Hamdhani Nurul Setiawan; Bayu Rizki Aufar; Muhamad Kahfi (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2023)
STEBI Global Mulia Cikarang Campus is a campus that conducts field practice and teaches students to create a business. KBN is one of the programs that can foster the entrepreneurial spirit of students. From opening a small business when we have serious intentions supported by all its aspects, it is not impossible that the business that is built will become big and continue to grow.The problem isn’t a few students work on this KBN just a formality. When they open a business, walk, then after the KBN period from campus is over, the students closed their businesses.We intend to provide education that graphic design is an important factor to support a business in the millennial era as it is today. Many of the students still don't understand that visual design is very helpful in developing the business they have. Just a small example that we usually see, such as banners, billboards, menu designs, Instagram feeds for digital marketing. These are all things that can help business actors, especially for KBN participants in STEBI Global Mulia, to develop. We intend to organize a graphic design seminar and class for STEBI Global Mulia students. Starting from us holding an introductory seminar, then continuing for practice, and consulting sessions related to graphic design for business development.